Bone marrow fat and the decline of B lymphopoiesis in rabbits. (May 2016) - Kennedy, Domenick E.; Witte, Pamela L.; Knight, Katherine L.
Abstract: B lymphopoiesis is necessary to generate a diverse pool of naïve B cells that are able to respond to a broad spectrum of antigens during immune responses to pathogens and to vaccination. Rabbits have been utilized for many years to generate high affinity monoclonal and polyclonal antibodies. Specific antibodies generated in rabbits have greatly advanced scientific discoveries, but the unique qualities of rabbit B cell development have been underappreciated. Unlike in humans and mice, where B lymphopoiesis declines in mid to late life, B lymphopoiesis in rabbits arrests early in life, between 2 and 4 months of age. This review focuses on the early loss of B cell development in rabbits and the contribution of the bone marrow microenvironment to this process. We also propose directions for future research in this area, and discuss how the rabbit can be used as a model to understand the decline of B lymphopoiesis that occurs in humans late in life. Such studies will be important for developing therapeutics targeted to prevent and/or reverse declining B lymphopoiesis in the elderly, as well as boosting immunity and antibody responses after infection or vaccination. Highlights: B lymphopoiesis declines in rabbit bone marrow early in life (2–4 months of age). Bone marrow fills with fat simultaneous to the decline in B lymphopoiesis. Rabbit is a unique model for studying the decline of B lymphopoiesis in humans.